Long-term Survival after Combined Epidural–General Anesthesia or General Anesthesia Alone: Follow-up of a Randomized Trial. (August 2021) - Du, Ya-Ting; Li, Ya-Wei; Zhao, Bin-Jiang; Guo, Xiang-Yang; Feng, Yi; Zuo, Ming-Zhang; Fu, Cong; Zhou, Wei-Jie; Li, Huai-Jin; Liu, Ya-Fei; Cheng, Tong; Mu, Dong-Liang; et al.
Abstract : Background: Experimental and observational research suggests that combined epidural–general anesthesia may improve long-term survival after cancer surgery by reducing anesthetic and opioid consumption and by blunting surgery-related inflammation. This study therefore tested the primary hypothesis that combined epidural–general anesthesia improves long-term survival in elderly patients. Methods: This article presents a long-term follow-up of patients enrolled in a previous trial conducted at five hospitals. Patients aged 60 to 90 yr and scheduled for major noncardiac thoracic and abdominal surgeries were randomly assigned to either combined epidural–general anesthesia with postoperative epidural analgesia or general anesthesia alone with postoperative intravenous analgesia. The primary outcome was overall postoperative survival. Secondary outcomes included cancer-specific, recurrence-free, and event-free survival. Results: Among 1, 802 patients who were enrolled and randomized in the underlying trial, 1, 712 were included in the long-term analysis; 92% had surgery for cancer. The median follow-up duration was 66 months (interquartile range, 61 to 80). Among patients assigned to combined epidural–general anesthesia, 355 of 853 (42%) died compared with 326 of 859 (38%) deaths in patients assigned to general anesthesia alone: adjusted hazard ratio, 1.07; 95% CI, 0.92 to 1.24; P = 0.408. Cancer-specific survival was similar with combined epidural–general anesthesia (327 of 853 [38%]) and general anesthesia alone (292 of 859 [34%]): adjusted hazard ratio, 1.09; 95% CI, 0.93 to 1.28; P = 0.290. Recurrence-free survival was 401 of 853 [47%] for patients who had combined epidural–general anesthesia versus 389 of 859 [45%] with general anesthesia alone: adjusted hazard ratio, 0.97; 95% CI, 0.84 to 1.12; P = 0.692. Event-free survival was 466 of 853 [55%] in patients who had combined epidural–general anesthesia versus 450 of 859 [52%] for general anesthesia alone: adjusted hazard ratio, 0.99; 95% CI, 0.86 to 1.12; P = 0.815. Conclusions: In elderly patients having major thoracic and abdominal surgery, combined epidural–general anesthesia with epidural analgesia did not improve overall or cancer-specific long-term mortality. Nor did epidural analgesia improve recurrence-free survival. Either approach can therefore reasonably be selected based on patient and clinician preference. Abstract : In patients aged 60 to 90 yr having major noncardiac thoracic and abdominal surgery, combined epidural–general anesthesia compared to general anesthesia alone did not improve overall or cancer-specific long-term survival. Combined epidural–general anesthesia also did not improve recurrence-free survival.Supplemental Digital Content is available in the text.